Generation of hiPSC-Derived Functional Dopaminergic Neurons in Alginate-Based 3D Culture - Gilmozzi, Valentina; Gentile, Giovanna; Riekschnitz, Diana A.; Von Troyer, Michael; Lavdas, Alexandros A.; Kerschbamer, Emanuela; Weichenberger, Christian X.; Rosato-Siri, Marcelo D.; Casarosa, Simona; Conti, Luciano; Pramstaller, Peter P.; Hicks, Andrew A.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Human induced pluripotent stem cells (hiPSCs) represent an unlimited cell source for the generation of patient-specific dopaminergic (DA) neurons, overcoming the hurdle of restricted accessibility to disease-affected tissue for mechanistic studies on Parkinson’s disease (PD). However, the complexity of the human brain is not fully recapitulated by existing monolayer culture methods. Neurons differentiated in a three dimensional (3D) in vitro culture system might better mimic the in vivo cellular environment for basic mechanistic studies and represent better predictors of drug responses in vivo. In this work we established a new in vitro cell culture system based on the microencapsulation of hiPSCs in small alginate/fibronectin beads and their differentiation to DA neurons. Optimization of hydrogel matrix concentrations and composition allowed a high viability of embedded hiPSCs. Neural differentiation competence and efficiency of DA neuronal generation were increased in the 3D cultures compared to a conventional 2D culture methodology. Additionally, electrophysiological parameters and metabolic switching profile confirmed increased functionality and an anticipated metabolic resetting of neurons grown in alginate scaffolds with respect to their 2D counterpart neurons. We also report long-term maintenance of neuronal cultures and preservation of the mature functional properties. Furthermore, our findings indicate that our 3D model system can recapitulate mitochondrial superoxide production as an important mitochondrial phenotype observed in neurons derived from PD patients, and that this phenotype might be detectable earlier during neuronal differentiation. Taken together, these results indicate that our alginate-based 3D culture system offers an advantageous strategy for the reliable and rapid derivation of mature and functional DA neurons from hiPSCs.